Zastosowanie analizy korespondencji do redukcji zmiennych opisujących działalność marketingową na przykładzie przedsiębiorstw przetwórstwa mięsnego - Soboń, Magdalena (Use of Correspondence Analysis to the Reduction of Variables Describing Marketing Activity on the Example of Meat Processing Enterprises, 2006)
Marketing activity is often analyzed with a help of a survey. The data set that is obtained this way can be reduced to a smaller, mutually not correlated variables set witch, however, is comparable with an input one. In order to achieve that a correspondence analysis is used that makes it possible to find hidden dimensions describing the researched phenomenon to a satisfying degree.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 515-522